A new species of Valeria Stephens, 1829 (Lepidoptera, Psaphidinae) from Iran - Gyulai, Péter (Zootaxa, 2019)
The description and diagnosis of Valeria wassalberti, sp. nov. are provided. The new species and the closely related species are illustrated with 2 imagines in colour and 3 female genitalia figures.